116 In level scheme and p-n configurations - Rabenstein, D.; Harrach, D.; Vonach, H.; Perazzo, R. P. J.; Dussel, G. G. (North Holland Publishing, 1972)
Fil: Rabenstein, D. Technische Universität München; Alemania